2018
DOI: 10.1136/archdischild-2017-314205
|View full text |Cite
|
Sign up to set email alerts
|

Human milk as a protective factor for bronchopulmonary dysplasia: a systematic review and meta-analysis

Abstract: Both exclusive human milk feeding and partial human milk feeding appear to be associated with lower risk of BPD in preterm infants. The quality of evidence is low. Therefore, more RCTs of this topic are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 37 publications
4
53
1
3
Order By: Relevance
“…Interestingly, breastfed infants have more abundant Lactobacilli and less abundant Proteobacteria compared to formula-fed infants (21), a similar differentiating feature of BPD-resistant infants compared to BPD-susceptible infants (16). Additionally, a meta-analysis comparing human milk to formula milk found decreased odds of BPD development in human milk-exposed infants (OR 0.78; 95% CI 0.68-0.88); however, the quality of evidence was low (26). More evidence is needed relating human milk to the airway microbiome given the overlap in microbial composition observed in breast milk-fed infants and BPD-resistant infants.…”
Section: What Factors Influence the Airway Microbiome?mentioning
confidence: 99%
“…Interestingly, breastfed infants have more abundant Lactobacilli and less abundant Proteobacteria compared to formula-fed infants (21), a similar differentiating feature of BPD-resistant infants compared to BPD-susceptible infants (16). Additionally, a meta-analysis comparing human milk to formula milk found decreased odds of BPD development in human milk-exposed infants (OR 0.78; 95% CI 0.68-0.88); however, the quality of evidence was low (26). More evidence is needed relating human milk to the airway microbiome given the overlap in microbial composition observed in breast milk-fed infants and BPD-resistant infants.…”
Section: What Factors Influence the Airway Microbiome?mentioning
confidence: 99%
“…Until recently, data suggesting a bene cial impact of maternal milk feeding on BPD were limited. Some investigators had concluded that maternal milk decreased incidence of BPD [7,[11][12][13][14], but others had not thought it useful [15]. Thus we can make two postulations: either high-volume maternal milk feeding daily directly impacts BPD or BPD has an obvious effect on volume maternal milk feeding .…”
Section: Discussionmentioning
confidence: 99%
“…Several meta-analyses comparing human milk or own mother's milk and any maternal milk with exclusive formula draw different conclusions, although most have found that exclusive breast milk feeding was associated with decreased incidence of BPD. Partially receiving breast milk has also been shown to provide a protective effect compared with exclusive formula feeding, but the level of evidence is not high [7,17]. Patel et al [18] revealed a 9.5% reduction in the odds of BPD for each 10% increase in enteral feedings consisting of mothers' milk received from birth to 36 weeks PMA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human milk plays a protective role towards the immature lung through various mechanisms including specific nutrients and factors, and through its influence on microbiota. A recent meta-analysis including 22 studies (17 cohort plus 5 RCTs) and 8661 infants [149] showed a trend towards a protective effect of human milk against BPD, calling for larger RCTs the determine a definite answer, which would undoubtedly raise ethical questions given its proven benefits in other diseases of prematurity such as necrotizing enterocolitis. In addition, differences exist between fresh maternal breast milk (MBM) and pasteurized human donor milk (DBM).…”
Section: Human Milkmentioning
confidence: 99%